Cardiac risk in non-cardiac surgery: A review. (August 2018) - Kindler, Manuel; Wanner, Patrick Mark; Filipovic, Miodrag
Abstract: International guidelines propose a stepwise workup for the assessment/risk stratification of patients undergoing non-cardiac surgery and guide further testing or treatment/optimization of underlying cardiovascular disease when appropriate. Despite optimal surgical and medical care, around one million patients worldwide will die annually shortly after having undergone a surgical procedure. A major contributor to this postoperative mortality are "silent myocardial ischemic events" which often go unrecognized. Routine measurement of cardiac biomarkers is an important step in the identification of high risk patients and in improving their perioperative care. Once an ischemic event has occurred, a multidisciplinary approach should guide management (e.g. optimization of anti-ischemic and plaque stabilizing therapy, anticoagulation, antiplatelet therapy or invasive strategies), keeping in mind the fragile balance between risk of ischemic events and bleeding. Highlights: Troponin elevation is a strong risk factor for 30- day mortality after (non-cardiac) surgery and always represents myocardial injury. The vast majority of patients with postoperative troponin elevations have no ischemic symptoms; those with clinical symptoms of cardiac ischemia have even higher 30-day mortality. High preoperative natriuretic peptide levels may identify high risk patients who require routine postoperative troponin measurements. The perioperative risk of patients with heart failure is underestimated.